1996
DOI: 10.1128/aac.40.4.958
|View full text |Cite
|
Sign up to set email alerts
|

Two or three days of ofloxacin treatment for uncomplicated multidrug-resistant typhoid fever in children

Abstract: An open randomized comparison of 2 days (Ofx2) versus 3 days (Ofx3) of oral ofloxacin treatment (15 mg/kg/ day) was conducted with Vietnamese children between 1 and 15 years of age with suspected typhoid fever. Of 108 children enrolled, 100 were blood culture positive for Salmonella typhi, and 86% of the isolates were multidrug resistant. There were no significant adverse effects. The therapeutic responses were similar in both groups, with mean (؎ standard deviation) fever clearances of 107 ؎ 60 h in the Ofx3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 13 publications
1
39
1
1
Order By: Relevance
“…[1][2][3][4] Approximately one-fourth of the strains (18/73) we used in this study were found to be resistant to chloramphenicol and cotrimoxazole. Above all, 12 strains were also resistant to amoxicillin by producing common TEM-1 type -lactamase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] Approximately one-fourth of the strains (18/73) we used in this study were found to be resistant to chloramphenicol and cotrimoxazole. Above all, 12 strains were also resistant to amoxicillin by producing common TEM-1 type -lactamase.…”
Section: Discussionmentioning
confidence: 99%
“…However, cephalosporins had been considered ineffective for the treatment of infectious diseases caused by bacteria growing in mammalian cells because of their low penetrability into such cells Recent clinical studies have shown the excellent efficacy of thirdgeneration cephalosporins 2,5-7 as well as new quinolones 4,[9][10][11][12] for typhoid fever, which can be considered a systemic infection rather than a local intestinal infection such as shigellosis. New quinolones should not be administered to pediatric patients for reasons of possible adverse drug reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical failures were: six in the 2-day ofloxacin regimen and two cases in the 3-day ofloxacin regimen (P > 0.2). There was an additional one case of relapse and one failed case [5].…”
Section: Typhoid Fevermentioning
confidence: 96%
“…This regimen not only has a high cure rate (> 97%) but also has a very low relapse and carrier rate (< 1%) [61•]. Although a 7-to 10-day course is recommended, shorter courses (2-3 days) are often successful, assuming the isolate is sensitive to quinolones [62][63][64]. Other quinolones, including norfloxacin, ofloxacin, and levofloxacin can also be used [61•,62,64,65].…”
Section: Treatmentmentioning
confidence: 99%